Prelude to a study of the feather mites of Australia (Acariformes: Astigmata) - Halliday, R.b. (Zootaxa, 2023)
This paper reviews the state of knowledge of the feather mites of Australia (Arachnida: Acariformes: Astigmata). The known fauna includes 149 species arranged in 95 genera and 24 families, in the Superfamilies Analgoidea and Pterolichoidea. A checklist of the fauna is provided, including bibliographic details for every species and genus. The bird host and collecting localities are listed for every species, and taxonomic and nomenclatural problems are discussed where necessary. The total fauna may include as many as 800 undescribed species. The checklist is preceded by a brief review of some aspects of the biology of feather mites, which have not been studied in the context of the Australian fauna.The correct spelling for a family of respiratory tract parasites is confirmed as Kytoditidae. Dabertia indistincta (Dabert & Atyeo, 1993) comb. n. (Syringobiidae) and Hemialges australis (Trouessart, 1885) comb. n. (Analgidae) are new combinations proposed herein.